PERFORMANCE OF THE BLATCHFORD SCORE IN PREDICTING OUTCOMES OF UPPER GASTROINTESTINAL BLEEDING DUE TO PEPTIC ULCER DISEASE IN THE EMERGENCY DEPARTMENT, DUC GIANG GENERAL HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical and laboratory characteristics of upper gastrointestinal bleeding patients and evaluate the Blatchford score’s prognostic value in predicting medical intervention requirements.Methods: A retrospective cross-sectional study of 53 patients with upper gastrointestinal bleeding due to peptic ulcer disease admitted to the Emergency Department of Duc Giang General Hospital from March to August 2025.Results: Mean age was 66.8 years with 83% male predominance. Blatchford score ≥ 6 was present in 90.6% of patients. Medical intervention was required in 73.6% of cases. At cutoff  ≥ 6, the score showed excellent sensitivity (100%), negative predictive value (100%), and accuracy (92.5%). Blatchford ≥ 6 points (OR = 15.8, p = 0.003) and high-risk Forrest classification IA-IIB (OR = 8.5, p = 0.007) were independent predictors of medical intervention.Conclusion: The Blatchford score is a valuable tool for early risk stratification in emergency settings, accurately identifying low-risk patients who may not require urgent intervention.
Keywords: Upper gastrointestinal bleeding, Blatchford score, peptic ulcer, medical intervention, emergency department.